The effect of e/a ratio on thermodynamic parameters and surface morphology of Cu-Al-Fe-X shape memory alloys (vol 89, pg 75, 2019) - Canbay, Canan Aksu; Aziz Baiz, Sivar; Ozkul, Iskender; Dere, Aysegul (Springer, 2020)
[Abstract Not Available]